2015
DOI: 10.18632/oncotarget.5003
|View full text |Cite
|
Sign up to set email alerts
|

The PTTG1-targeting miRNAs miR-329, miR-300, miR-381, and miR-655 inhibit pituitary tumor cell tumorigenesis and are involved in a p53/PTTG1 regulation feedback loop

Abstract: Deregulation of the pituitary tumor transforming gene (PTTG1), a newly discovered oncogene, is a hallmark of various malignancies, including pituitary tumors. However, the mechanisms regulating PTTG1 expression are still needed to be explored. MicroRNAs (miRNAs) are a novel class of small RNA molecules that act as posttranscriptional regulators of gene expression and can play a significant role in tumor development. Here, we identified a series of miRNAs, namely, miR-329, miR-300, miR-381 and miR-655, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 55 publications
3
71
0
2
Order By: Relevance
“…Because the parent genes PTTG1 and PTTG2 were previously confirmed to be oncogenes in various cancer types 11, 15, 16, 17 and PTTG3P shares high similarity with these genes (Fig. S1), we suggested that PTTG3P plays a role in modulating PTTG1 or PTTG2 that is similar to previously reported mechanisms 18, 19.…”
Section: Resultssupporting
confidence: 85%
“…Because the parent genes PTTG1 and PTTG2 were previously confirmed to be oncogenes in various cancer types 11, 15, 16, 17 and PTTG3P shares high similarity with these genes (Fig. S1), we suggested that PTTG3P plays a role in modulating PTTG1 or PTTG2 that is similar to previously reported mechanisms 18, 19.…”
Section: Resultssupporting
confidence: 85%
“…It is reported that miR-93 can repress apoptosis after cerebral ischemia via interleukin-1 [38]. Similarly, a previous study proved that miR-381 was overexpressed in the mature brain and normal hippocampal neurons [13], and decreasing miR-381 expression inhibited cell proliferation and invasion [39, 40], from which we inferred that up-regulation of miR-381 inhibited neuronal apoptosis.…”
Section: Discussionsupporting
confidence: 63%
“…It is discovered that down-regulation of miR-381 in colon cancer tissues leads to up-regulation of LRH-1 and induces proliferation and invasion of colon cancer cells (22). In addition, miR-381, which is present in the p53/PTTG1 negative feedback loop, can inhibit the growth of pituitary adenomas (23). miR-381 is closely related to MDR1 gene and plays an important role in multidrug resistance (24).…”
Section: Discussionmentioning
confidence: 99%